Peranan Freight Forwarding dalam Pengurusan Dokumen Ekspor pada PT. Samudera Lautan Luas Medan - Royzaldi Royzaldi; Fadiyah Hani Sabila; Nurmaliana Sari Siregar (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This research aims to analyze the role of Freight Forwarding (FF) in export document management at PT. Samudera Lautan Luas Medan. The process begins with shipping planning between ports, with documents being the primary requirement for export activities. PT. Samudera Lautan Luas Medan handles all documents involving various parties such as exporters, importers, shipping companies, banks, customs, and related agencies. Key documents include proforma shipping instructions, invoices, packing lists, bills of lading, and other supporting certificates. As a freight forwarding company, they act as the exporter's representative in managing export documents. The company requires supplementary documents from the exporter to complete the process. Recommendations include improving document accuracy, developing human resources in technology, and enhancing infrastructure to achieve professional freight forwarding performance.